TANTANGAN DAN SOLUSI PERLINDUNGAN KONSUMEN DALAM TRANSAKSI DIGITAL: PERSPEKTIF HUKUM BISNIS DI INDONESIA - Amaanulloh, Ilham Syuhada; Haq, Bahrul; Satrio, Matin Dimas (Taksasila Edukasi Insani, 2025)
The rapid development of the digital world and e-commerce has changed the dynamics of global trade, including in Indonesia. Although technology has brought convenience and efficiency to consumers, consumer protection in digital transactions still faces a number of challenges. This study aims to analyze consumer protection in digital transactions based on the perspective of business law in Indonesia. This study also discusses how the application of business law principles, including Islamic law, can strengthen existing regulations to ensure fair and transparent digital transactions.Keywords: consumer protection, and e-commerce, Digital transactions